2018
DOI: 10.1159/000493086
|View full text |Cite
|
Sign up to set email alerts
|

Round Window Niche Drilling with Intratympanic Steroid Is a Salvage Therapy of Sudden Hearing Loss

Abstract: Objective: To explore the effectiveness and safety of round window niche drilling combined with intratympanic methylprednisolone injection for the salvage treatment of sudden sensorineural hearing loss (SSNHL) and its associated tinnitus after failed primary treatment. Method: SSNHL patients who showed a less than 10-dB improvement of pure-tone average after receiving standard systemic treatment and intratympanic steroid injection were enrolled. All included patients were randomly divided into two groups (cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…After assessing the remaining 99 full-text articles, 41 studies were excluded for the following reasons: foreign language (n = 3), case reports (n = 3), review or meta-analysis (n = 10), and no mention of complications (n = 25). Finally, 58 studies 1-5,9-61 were included in the systemic review and meta-analysis including 25 randomized controlled trials, 10 prospective studies, and 22 retrospective case-controlled studies ( Table 1 ). A total of 2824 patients served as participants in the meta-analysis wherein 2567 received ITSI via TC (54 articles) and 257 received ITSI via VT (4 articles).…”
Section: Resultsmentioning
confidence: 99%
“…After assessing the remaining 99 full-text articles, 41 studies were excluded for the following reasons: foreign language (n = 3), case reports (n = 3), review or meta-analysis (n = 10), and no mention of complications (n = 25). Finally, 58 studies 1-5,9-61 were included in the systemic review and meta-analysis including 25 randomized controlled trials, 10 prospective studies, and 22 retrospective case-controlled studies ( Table 1 ). A total of 2824 patients served as participants in the meta-analysis wherein 2567 received ITSI via TC (54 articles) and 257 received ITSI via VT (4 articles).…”
Section: Resultsmentioning
confidence: 99%
“…In our examination, we chose intravenous dexamethasone in an effort to achieve a higher drug concentration, using intratympanic methylprednisolone for its better diffusion coefficient, longer elimination halftime, and its ability to regulate sodium transport and reabsorption in the inner ear. 25 Accumulating evidence has indicated that the early intervention is an important prognostic factor in the therapy of SSNHL. Statistically significantly different response rates (76.1% vs 50%) were established between the early treatment group and the delayed treatment group in a retrospective study with 176 SSNHL patients who received intratympanic steroid injection.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the oral or intravenous steroids are not recommended for pregnant patients because the prenatal exposure can cause detrimental effects in the fetus. Intratympanic dexamethasone injection is otherwise safe and efficient due to high-precision delivery to the cochlear fluids without systematic absorption, high local concentration, and long duration of medication action that regulates sodium transport and reabsorption in the inner ear [ 21 ]. Fu et al[ 22 ] conducted a prospective study on intratympanic dexamethasone for SSNHL in pregnancy with a curative rate (CR + PR) of 33%, and their single dosage was 4 mg at various times of injections according to the pure-tone audiogram improvements[ 22 ].…”
Section: Discussionmentioning
confidence: 99%